2021
DOI: 10.1039/d0nh00538j
|View full text |Cite
|
Sign up to set email alerts
|

Real-time insight into nanostructure evolution during the rapid formation of ultra-thin gold layers on polymers

Abstract: Ultra-thin metal layers on polymer thin films attract tremendous research interest for advanced flexible optoelectronic applications, including organic photovoltaics, light emitting diodes and sensors. To realize the large-scale production of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 61 publications
0
33
0
Order By: Relevance
“…The same group investigated the evolution of Ag films on PMMA- b -poly­(3-hexylthiophene-2,5-diyl) (PMMA- b -P3HT) and Cu films on PS- b -PEO, identifying the importance of reactions with the polymer, implantation of the metal into the polymer, and surface mobility. These factors also influence nanostructure formation in metals on homopolymer surfaces as do the roughness and density of the polymer surface, the metal deposition rate, film thickness, and changes to the polymer induced by the deposition process such as chain scission or cross-linking. , For Cu on (PS- b -PEO), four growth stages were identified consisting of nucleation, growth driven by diffusion, growth driven by adsorption, and grain growth. Gopinathan modeled metal nanostructure formation, pointing out the importance of kinetics and surface mobility contrast in determining the final structure.…”
Section: Introductionmentioning
confidence: 99%
“…The same group investigated the evolution of Ag films on PMMA- b -poly­(3-hexylthiophene-2,5-diyl) (PMMA- b -P3HT) and Cu films on PS- b -PEO, identifying the importance of reactions with the polymer, implantation of the metal into the polymer, and surface mobility. These factors also influence nanostructure formation in metals on homopolymer surfaces as do the roughness and density of the polymer surface, the metal deposition rate, film thickness, and changes to the polymer induced by the deposition process such as chain scission or cross-linking. , For Cu on (PS- b -PEO), four growth stages were identified consisting of nucleation, growth driven by diffusion, growth driven by adsorption, and grain growth. Gopinathan modeled metal nanostructure formation, pointing out the importance of kinetics and surface mobility contrast in determining the final structure.…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved GISAXS studies have particularly benefited from the development of fast detectors, reaching sub-millisecond time scales. [304] In an early demonstration, this enabled studying assemblies in drying liquid drops where a critical drop size was found that is necessary for the assembly of iron oxide NPs. [278] In the following, particular interest was spent on studying the assemblies of quantum dots, such as PbS, [108,225,298,299] and PbSe [291][292][293] with GISAXS, but also iron oxide NPs [279] and semiconductor nanorods.…”
Section: Self-assembly At Interfacesmentioning
confidence: 99%
“…These drawbacks, which can appear in the chemical approach, can be avoided using a different NP synthesis method: sputtering of the desired metals on ionic liquids (ILs), which combines a well-developed deposition technique with a comparable new substrate class. , Sputtering is a very versatile deposition method, in terms of possible materials to be deposited and for the choice of different substrates covering all materials classes including polymers and most recently ILs. Another advantage of sputter deposition of thin films is that bulk-immiscible multinary systems can be fabricated as forced solid solutions by co-sputtering .…”
Section: Introductionmentioning
confidence: 99%